Environment in the lives of children and families - Phoenix, Ann (Policy Press, 2017)
Epdf available Open Access under CC-BY licence. Based on involved creative, qualitative work with families in India and the UK who live in different contexts, this book illuminates how environmental practices are negotiated within families, and how they relate to values, identities, and society. It contributes to understanding of the ways in which families and childhood are constructed as sites for intervention in climate change debates.